1985
DOI: 10.1111/j.1600-0447.1985.tb01283.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of concurrent benzodiazepine administration to seizure duration in ECT

Abstract: The relationship of concurrent benzodiazepine administration to seizure duration in ECT was examined. Administration of a standard oral dose of 10 mg diazepam to a series of patients suffering from major depressive disorder produced a significant reduction in men seizure length during ECT compared to length of ECT-induced seizure in those patients when they were benzodiazepine free. This finding is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…Although earlier studies suggested that this combination reduced the number of ECT treatments, this has not been confirmed by others [25,37]. Our results also confirm earlier reports that benzodiazepines affect seizure threshold [26,28] and duration. Patients taking benzodiazepines had seizures that were on average 4.6 seconds shorter than those not taking them.…”
Section: Discussionsupporting
confidence: 90%
“…Although earlier studies suggested that this combination reduced the number of ECT treatments, this has not been confirmed by others [25,37]. Our results also confirm earlier reports that benzodiazepines affect seizure threshold [26,28] and duration. Patients taking benzodiazepines had seizures that were on average 4.6 seconds shorter than those not taking them.…”
Section: Discussionsupporting
confidence: 90%
“…Second, sex and medication influence ST, but they are less potent than age . Benzodiazepines have been found to cause a shorter seizure duration in several studies . Pettinati et al .…”
Section: Discussionmentioning
confidence: 99%
“…The anticonvulsant effect of ECT may therefore account for a shortening of fit length in the benzodiazepine group. Similar methodological problems may account for Standish-Barry, Deacon and Snaith's (1985) finding, that seizure length during the third and fourth ECT treatment for patients on benzodiazepines was shortened when compared with seizure length during the first and second treatment when not on benzodiazepines. Gassy and Rey (1990) suggest that women tend to have lower seizure thresholds and significantly longer seizure lengths than men.…”
Section: Discussionmentioning
confidence: 78%
“…The effect of psychotropic drugs on seizure duration is of particular interest as these drugs can be altered by the attending physician. A number of studies report that benzodiazepines cause a reduction in fit length and consequently interfere with the therapeutic effects of ECT (Stromgren et al, 1980;d'Elia, 1982;Standish-Barry, Deacon and Snaith, 1985;Cohen and Lawton, 1992). Carbamazepine, sodium valproate and to a lesser extent clonazepam are commonly used as mood stabilizers in patients with severe affective disorders or in those patients where other treatments have proven difficult.…”
Section: Introductionmentioning
confidence: 97%